Adenoassociated Virus Type 2-Induced Inhibition of the Human Papillomavirus Type 18 Promoter in Transgenic Mice (2002)
ABSTRACT : The epithelium of the cervix uteri has been reported to be frequently coinfected with both human papillomaviruses (HPV) and helper virus-dependent adenoassociated viruses (AAV). Seroepidemiological data suggest that AAV infection could inhibit cervical cancer that is caused by specific (“high-risk”) types of papillomaviruses. In vitro, infection with AAV type 2 (AAV-2) or transfection of AAV-2 early (rep) genes has been shown to inhibit transformation by papillomaviruses. To analyze the effects of AAV on HPV in vivo, we studied the influence of AAV-2 infection on the promoter activity of high-risk HPV type 8 (HPV-18) in mice, transgenic for sequences of the upstream regulatory region (URR) of HPV-18 controlling transcription of the reporter gene, lacZ. Transgenic animals (or tongue cells thereof, explanted and grown in culture) were treated with dexamethasone to induce the HPV-18 promoter. Simultaneously they were (i) infected with AAV, (ii) inoculated with AAV virus-like particles (VLPs; empty capsids), or (iii) mock infected. Inoculation with AAV-2 or VLPs inhibited activation of the HPV-18 promoter. In vitro, in baby hamster kidney cells transfected with the HPV-18-lacZ construct, tissue extracts from AAV-infected animals suppressed the HPV-18 URR to a similar extent as AAV infection did. Down-regulation of the HPV-18 promoter was less efficient with extracts from animals inoculated with VLPs and was not observed with extracts from uninfected or dexamethasone-treated animals. This indicates that AAV induces cellular factor(s) in vivo capable of mediating down-regulation of the HPV-18 promoter also in cells in vitro. In contrast, promoters of the low-risk HPV types (HPV-6, HPV-11) were not influenced by AAV infection as opposed to promoters of the high-risk types (HPV-18 and HPV-16).